Study of Hepatitis E Virus-4 Infection in Human Liver-Chimeric, Immunodeficient, and Immunocompetent Mice - Collignon, Laura; Verhoye, Lieven; Hakze-Van der Honing, Renate; Van der Poel, Wim H. M.; Meuleman, Philip (Frontiers in Microbiology, 2022)
The hepatitis E virus (HEV) is responsible for 20 million infections worldwide per year. Although, HEV infection is mostly self-limiting, immunocompromised individuals may evolve towards chronicity. The lack of an efficient small animal model has hampered the study of HEV and the discovery of anti-HEV therapies. Furthermore, new HEV strains, infectious to humans, are being discovered. Human liver-chimeric mice have greatly aided in the understanding of HEV, but only two genotypes (HEV-1 and HEV-3) have been studied in this model. Moreover, the immunodeficient nature of this mouse model does not allow full investigation of the virus and all aspects of its interaction with the host. Recent studies have shown the susceptibility of regular and nude Balb/c mice to a HEV-4 strain (KM01). This model should allow the investigation of the interplay between HEV and the adaptive immune system of its host, and potential immune-mediated complications. Here, we assess the susceptibility of human liver-chimeric and non-humanised mice to a different HEV-4 strain (BeSW67HEV4-2008). We report that humanised mice could be readily infected with this isolate, resulting in an infection pattern comparable to HEV-3 infection. Despite these results and in contrast to KM01, non-humanised mice were not susceptible to infection with this viral strain. Further investigation, using other HEV-4 isolates, is needed to conclusively determine HEV-4 tropism and mouse susceptibility.